O20.5 Trends in undiagnosed hiv and hiv testing behaviour in community samples of men who have sex with men in london, uk: results from repeat cross-sectional surveys between 2000–2013. (13th September 2015) - Wayal, Sonali; Parsons, V; Copas, A; Danielle, M; Nardone, A; Aghaizu, A; Hart, G; Gilson, R; Johnson, AM
Abstract : Background: HIV testing can reduce undiagnosed and late HIV diagnosis. We examine trends between 2000–2013 of overall and undiagnosed HIV prevalence, HIV testing among men who have sex with men (MSM), and factors associated with undiagnosed HIV. Methods: Repeat cross-sectional anonymous behavioural surveys with oral specimens for HIV antibody (Ab) testing were conducted in community venues in London. Participants were treated as undiagnosed HIV+ if they tested HIV Ab+, and had never tested for HIV, last tested or perceived themselves as HIV negative, or did not know their HIV status. Undiagnosed fraction is the proportion of undiagnosed HIV Ab+ results of the total number of HIV Ab+ results. Trends between 2000–2013 and factors associated with undiagnosed HIV (2011 and 2013 data) were examined using logistic regression. Adjusted odds ratios (AOR) and 95% confidence intervals (CI) were calculated.  Results: The majority of the 11876 participants included in the analysis were White, employed, and median age was 33 years. In 2013, overall and undiagnosed HIV prevalence was 13.6% (106/782) and 3.2% (25/782) respectively. Overall undiagnosed fraction remained unchanged: 34% (45/131) in 2000 and 24% (25/106) in 2013. Undiagnosed fraction among sexual health clinic non-attenders in last year remained unchanged: 62% (23/37) in 2000; 59% (10/17) in 2013. HIV testing in the last year increased: 26% (263/997) to 60% (467/777); among undiagnosed HIV+ men, it increased from 28.6% (10/35) to 66.7% (16/24). Compared to men aged >45, men aged 15–25 (AOR: 7.47, 95% CI: 1.56–35.74); compared to sexual health clinic attenders in the last year, non-sexual health clinic attenders (AOR: 4.39, 95% CI: 1.90–10.16) were more likely to have undiagnosed HIV. Conclusions: HIV testing has increased yet undiagnosed HIV remains unchanged. Strategies to increase HIV testing among young MSM and in non-sexual health clinics should be developed and evaluated. Declaration of interest statement: AMJ has been a Governor of the Wellcome Trust since 2011. The other authors declare that they have no conflicts of interest.